Hepatotoxic potential of asarones: in vitro evaluation of hepatotoxicity and quantitative determination in herbal products - Patel, Dhavalkumar N.; Ho, Han K.; Tan, Liesbet L.; Tan, Mui-Mui B.; Zhang, Qian; Low, Min-Yong; Chan, Cheng-Leng; Koh, Hwee-Ling (Frontiers in Pharmacology, 2015)
α and β asarones are natural constituents of some aromatic plants, especially species of the genus Acorus. In addition to beneficial properties of asarones, genotoxicity and carcinogenicity are also reported. Due to potential toxic effects of β-asarone, a limit of exposure from herbal products of approximately 2 μg/kg body weight/day has been set temporarily until a full benefit/risk assessment has been carried out by the European Medicines Agency. Therefore, it is important to monitor levels of β-asarone in herbal products. In this study, we developed a simple, rapid and validated GC-MS method for quantitative determination of asarones and applied it in 20 pediatric herbal products after detecting high concentrations of β-asarone in a product suspected to be implicated in hepatotoxicity in a 3 month old infant. Furthermore, targeted toxicological effects were further investigated in human hepatocytes (THLE-2 cells) by employing various in vitro assays, with the goal of elucidating possible mechanisms for the observed toxicity. Results showed that some of the products contained as much as 4 to 25 times greater amounts of β-asarone than the recommended levels. In 4 of 10 samples found to contain asarones, the presence of asarones could not be linked to the labeled ingredients, possibly due to poor quality control. Cell-based investigations in THLE2 cells confirmed the cytotoxicity of -asarone (IC50 = 40.0 ± 2.0 µg/mL) which was associated with significant lipid peroxidation and glutathione depletion. This observed cytotoxicity effect is likely due to induction of oxidative stress by asarones. Overall, the results of this study ascertained the usability of this GC-MS method for the quantitative determination of asarones from herbal products, and shed light on the importance of controlling the concentration of potentially toxic asarones in herbal products to safeguard consumer safety. Further investigations of the toxicity of asarones are warranted.